Lifestyle factors and high-risk atherosclerosis: Pathways and mechanisms beyond traditional risk factors. (March 2020) - Lechner, Katharina; von Schacky, Clemens; McKenzie, Amy L; Worm, Nicolai; Nixdorff, Uwe; Lechner, Benjamin; Kränkel, Nicolle; Halle, Martin; Krauss, Ronald M; Scherr, Johannes
Despite major efforts to reduce atherosclerotic cardiovascular disease (ASCVD) burden with conventional risk factor control, significant residual risk remains. Recent evidence on non-traditional determinants of cardiometabolic health has advanced our understanding of lifestyle–disease interactions. Chronic exposure to environmental stressors like poor diet quality, sedentarism, ambient air pollution and noise, sleep deprivation and psychosocial stress affect numerous traditional and non-traditional intermediary pathways related to ASCVD. These include body composition, cardiorespiratory fitness, muscle strength and functionality and the intestinal microbiome, which are increasingly recognized as major determinants of cardiovascular health. Evidence points to partially overlapping mechanisms, including effects on inflammatory and nutrient sensing pathways, endocrine signalling, autonomic function and autophagy. Of particular relevance is the potential of low-risk lifestyle factors to impact on plaque vulnerability through altered adipose tissue and skeletal muscle phenotype and secretome. Collectively, low-risk lifestyle factors cause a set of phenotypic adaptations shifting tissue cross-talk from a proinflammatory milieu conducive for high-risk atherosclerosis to an anti-atherogenic milieu. The ketone body ß-hydroxybutyrate, through inhibition of the NLRP-3 inflammasome, is likely to be an intermediary for many of these observed benefits. Adhering to low-risk lifestyle factors adds to the prognostic value of optimal risk factor management, and benefit occurs even when the impact on conventional risk markers is discouragingly minimal or not present. The aims of this review are (a) to discuss novel lifestyle risk factors and their underlying biochemical principles and (b) to provide new perspectives on potentially more feasible recommendations to improve long-term adherence to low-risk lifestyle factors.